Practical Manual of Abdominal Organ Transplantation - Manzarbeitia, Cosme. (Springer US, 2002)
Abdominal organ transplantation, specifically liver, kidney and pancreatic transplantation, has experienced a tremendous growth over the last two decades. With this growth comes a need for a general, standardized introduction for those healthcare professionals involved with this branch of medicine. This manual is a readily-available, concise reference for the professional involved in the field of abdominal organ transplantation as well as the lay person. The Practical Manual of Abdominal Organ Transplantation covers the latest developments in organ procurement and transplantation as well as newer approaches to the organ shortage and the increasing use of liver donation. This practical manual serves as an invaluable tool for those in the medical profession, whether a student, resident or practitioner, working with abdominal organ transplantation and its effects on their patients. This manual includes concise and directed topics covering: - end-stage abdominal organ disease;.